Lymphoepithelial Cyst, A Diagnostic Dilemma: Case Report - Gill, Meenu; Chhabra, Sonia; Singh, Sunita; Mehrotra, Dimple; Rawat, Priyanka (Annals of Pathology and Laboratory Medicine, 2020)
Lymphoepithelial cysts are benign, slowly growing unilocular or multilocular lesions that appear in the head and neck region. They are also called branchial cysts and occur due to lymphocyte induced cystic ductular dilatation. The confirmatory diagnosis is always made on histopathological examination after resection. A 29 years old female patient presented to ENT department, Pt B. D. Sharma PGIMS, Rohtak with a soft to firm, non-tender, swelling in the submandibular region since 2 -3 days and was referred to Department of Pathology for FNAC on which a differential diagnosis of infected epidermoid cyst or squamous cell carcinoma was made and excision biopsy for confirmation and categorization was advised. The swelling was then excised and sent for histopathological examination and a final diagnosis of Lymphoepithelial cyst was made. The confirmatory diagnosis is always made postoperatively by histopathological examination. The treatment of a lymphoepithelial cyst is the surgical approach, which includes complete enucleation of the cyst. This is a case report of a lymphoepithelial cyst diagnosed on histopathology specimen for which differential of Infected cyst or Squamous cell carcinoma was given. The authors intend to highlight the importance of early histopathological diagnosis of Benign LEC as it has been reported to undergo malignant transformation